A feasibility study of a Family Focused Treatment for Adolescents with Bipolar Disorder—the FAB study. Issue 1 (December 2015) - Neely, Joanne; Miklowitz, David; Le Couteur, Ann; Ryan, Vicky; Vale, Luke; McGovern, Ruth; Sharma, Aditya
Abstract Background The aim of this study is to examine the feasibility of a future definitive randomised controlled trial of Family Focused Treatment for Adolescents UK (FFT-A UK) in the management of early-onset bipolar disorder (EOBD) (under 18 years). The FFT-A has been evaluated in the USA to augment the pharmacological treatment of adolescents with bipolar disorder (BD). The FFT-A UK has been condensed to 16 sessions over approximately 6 months to be utilised within the UK National Health Service. Research from the USA suggests that families experience high levels of distress, stress, burden and family disharmony when living with a young person who has BD. The FFT-A UK is a family-based approach designed to increase understanding of BD (psycho-education), improve communication and increase ability to problem-solve. Methods/Design The trial will examine the feasibility of a randomised, parallel group, non-blinded design and the procedures of a subsequent definitive trial. Thirty-three young people with BD and their families will be recruited. Participants will complete measures at baseline, on completion of the 6-month treatment and again after a further 6 months. The self-report measures include the Warwick Edinburgh Mental Well-being Scale, The McMaster Family Assessment Device (FAD), Conflict Behaviour Questionnaire aka 'Interaction Behaviour Questionnaire', EuroQuol EQ-5D-3L and EQ-5D-Y. Primary outcomes will be rates of eligibility, recruitment and retention, estimates of the variability in the self-report measures and assessment of the intervention delivery in the study population. Participants' qualitative views on the measures and intervention will be sought to confirm the acceptability of intervention and study design. The health economics component will establish how cost-effectiveness will be assessed in a future definitive trial. Discussion The study will produce a full trial protocol and amendments to the FFT-A UK to inform a well-designed multi-centre randomised controlled trial (RCT) as an adjunct to pharmacotherapy in the management of EOBD. Trial registration Current Controlled TrialsISRCTN59769322